Tipos celulares no córtex medial do lagarto Tropidurus hispidus - Almeida, Fabrício Tavares Cunha de (2007)
The aim of this study was to characterize the ependymal cells and neural population in the Tropidurus hispidus medial cortex. It s well known nowadays that the nervous system isn t so constant the way was believed and detains morphological and functional properties that was influenced by environmental, sexual, age alterations and origin of the lesion like others. There s a vast literature about studies of amphibians, birds, reptiles even mammals brains, but one of the major difficulties found in the nervous system s plasticity research area is the appropriated experimental model. The medial cortex of Tropidurus hispidus specimens was studied by several techniques as TIMM, Nissl, immunostainings to BrDU, GABA, EC40, by Lectin and mainly the Golgi method. The test results showed the existence of 17 neuronal types in the T. hispidus medial cortex, with the major prevalence of the unipolar granular neuron, showed 12 ependymal cells, showed the positive reactivity to the GABA, BrDU and EC40 immunostainings too, the two lasts shows a post-natal neurogenic activity in the cortical region of this animal. Also was positive reactivity to the Lectin utilization in the microglia visualization. With the analysis of all this aspects, the study in the Tropidurus hispidus medial cortex showed a structural complexity as other characteristics that turn this animal a viable experimental model to the neurogenic processes studies.